20.0k views
0 votes
Simplify the polynomial expressions by combining like terms and then multiply the resulting binomial expressions to find their product (6x-9)(8+5x-5)

User Mike Fuchs
by
5.8k points

2 Answers

3 votes

(6x-9)(8+5x-5)=(6x-9)(5x+3)=


=6x\cdot5x-5x\cdot9+6x\cdot3-9\cdot3=\\=30x^2-27x-27


User MarcGV
by
5.5k points
7 votes

Answer: 20x squared -33x-27

Step-by-step explanation: So u have (6x-9-2x) (8+5x-5) first you want to combine like terms. 6x-2x = 4x and 8-5 = 3 so u end up with (4x-9) (3+5x) if u follow the FOIL method u will end up with 12x+20x squared -27-45x. Last combine like terms again and the answer is 20x squared -33x-27 and I got the answer correct on Edmentum.

User Tom Teman
by
5.9k points